ANALISIS DAMPAK COVID-19 TERHADAP KESEJAHTERAAN PEDAGANG KAKI LIMA DI WISATA KULINER MAROS - Rahma Rais; Muhammad Iqbal Latief; Suryanto Arifin (Department of Sociology Faculty of Social and Political Sciences, 2021)
The purpose of this study is to determine the social conditions of street vendors after the covid-19 pandemic and describe the impact of covid-19 on the welfare of street vendors in Maros Culinary Tourism. The subjects in this study were the street vendors in Maros Culinary Tourism as many as 6 people and 1 from the Department of Culture and Tourism of Maros Regency. The research approach used was qualitative, which starts with the data and leads to conclusions. The purpose of the research used was descriptive, namely to make a systematic, factual and accurate description of the existing phenomena, or the relationship between the phenomena studied without any special treatment. The research base used was the case study method which aims to collect and analyze a certain process related to the research focus. Therefore, it can find a certain scope. The results of the study showed that the social conditions of the street vendors after the COVID-19 pandemic have changed greatly as a result of policies made by the government, namely the lack of income that affects the fulfillment of daily needs. In strong social relations when working together, supporting each other, while weak when unhealthy competition arises, there is jealousy regarding the implementation of policies that are not comprehensive. The process of adaptation occurs related to the schedule of opening and closing in culinary tourism areas, that is the occurrence sales arrangements issued by authorities and the integration process. The social impact of the closure and social restriction policies is the limited socialization process that creates problems and social relations even become competition and conflict between traders because of these policies The impact of culture on changing habits is from conventional (face to face) to online with delivery policy. The economic impact is a condition of reduced income and narrowing the space to work in culinary tourism because they are no longer able to open so they are forced to lay off employees or close street vendors' stalls so they look for other alternative jobs such as vegetable sellers, online shops, and barbers. Keywords : Social Impact, Covid 19, Welfare, Street Vendors